MOTIVASI AMERIKA SERIKAT MENGHALANGI CPO (Crude Palm Oil) INDONESIA MASUK KE DALAM EG List (Environmental Good List) APEC TAHUN 2012 - Djamhur, Ayu El Suraya; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research discuss about USA reason reject indonesia CPO to be in Eg list in 2012. Eg list is a list contained 54 categories of environmental goods products and will be able to minimize tariff max 5% at the end of 2015. Eg list was formed in the Vladivostok in 2012.This research is qualitative research that the data is taken from books, internet, journals and same related thesis. This research uses neo-mercantilism perspective and protectionism theory to analyze the object of research.The result of this research shows that USA motivation to block cpo from indonesia enter to eg list is to protect plant oil/vegetable oil producer intheir country because cpo is the biggest producers of plant oil today and defeat USA plant oil production. One of the way is by promoting black campaign and reject indonesia cpo to enter eg list of apec in 2012.Keywords: CPO,EG List, APEC,black campaign